Dinamika Spatiotemporal Perubahan Tutupan Lahan dan Indeks Keberlanjutan Lokal Kabupaten Cianjur, Jawa Barat - Rizqullah, Muhamad Fiqri; Rustiadi, Ernan; Rosandi, Vely Brian; Pravitasari, Andrea Emma; Muhamad Fiqri Rizqullah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Rapid land cover changes, primarily driven by urbanization and deforestation, present critical sustainability challenges for rural landscapes, especially in developing regions such as Cianjur Regency, West Java. These transitions threaten ecological integrity, disrupt water resource systems, and compromise biodiversity, ultimately impacting land productivity and sustainable development goals. This research adopts an integrated spatial analysis framework to quantify land cover transitions and assess their impacts on local sustainability through a multi-dimensional Local Sustainability Index (LSI). The study evaluates economic, social, and environmental sustainability at the village level by utilizing overlay analysis, Local Indicators of Spatial Autocorrelation (LISA), and clustering techniques. Findings indicate a pronounced shift, with rice fields reduced by approximately 29,212.6 ha over a decade (2011-2021), while dry agricultural and residential lands expanded by 43,428.5 ha and 4,889.7 ha, respectively. LSI analysis reveals a decline in high-category environmental sustainability, contrasted by an increase in social and economic LSI scores. Southern development area (WP) exhibits high environmental sustainability, while northern development area (WP) has high social welfare and economic growth (Cianjur, Cipanas, dan Pacet Sub-District). Spatial clustering results highlight four distinct village typologies: urban village (Cluster One), developing village (Cluster Two), good environmental village (Cluster Three), and underdeveloped village (Cluster Four).